2015
DOI: 10.1175/jtech-d-14-00059.1
|View full text |Cite
|
Sign up to set email alerts
|

Wind Measurements from Arc Scans with Doppler Wind Lidar

Abstract: Defining optimal scanning geometries for scanning lidars for wind energy applications remains an active field of research. This paper evaluates uncertainties associated with arc scan geometries and presents recommendations regarding optimal configurations in the atmospheric boundary layer. The analysis is based on arc scan data from a Doppler wind lidar with one elevation angle and seven azimuth angles spanning 30° and focuses on an estimation of 10-min mean wind speed and direction. When flow is horizontally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 39 publications
1
55
1
Order By: Relevance
“…Use of arc scans adds two additional parameters to the scanning geometry: (1) the arc span (i.e., the width of the scan sector, θ ) and (2) the angle between the center of the arc and the wind direction, which is a measure of the orientation of the arc scan and will be called hereafter the relative direction and denoted as β. The selection of these parameters have implications for the accuracy of the retrieved wind speed (Courtney et al, 2014;Wang et al, 2015). Here we extend prior work on optimizing scan geometry to minimize the uncertainty in the estimated wind speeds.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…Use of arc scans adds two additional parameters to the scanning geometry: (1) the arc span (i.e., the width of the scan sector, θ ) and (2) the angle between the center of the arc and the wind direction, which is a measure of the orientation of the arc scan and will be called hereafter the relative direction and denoted as β. The selection of these parameters have implications for the accuracy of the retrieved wind speed (Courtney et al, 2014;Wang et al, 2015). Here we extend prior work on optimizing scan geometry to minimize the uncertainty in the estimated wind speeds.…”
Section: Introductionmentioning
confidence: 86%
“…The gray dots show the observed radial velocity variance approximated by the difference between the variance and the autocovariance at one time lag of the radial velocities collected in an experiment in which the lidar was operated with a staring mode at the US National Renewable Energy Laboratory (Wang et al, 2015), and the observed CramerRao Bound (CRB) (filled dark circles) is approximated by the mean of the lowest 5 % of the gray dots (Frehlich, 2001). The empirical relationship between the SNR and the CRB is denoted by the dark solid line and is based on Eq.…”
Section: Uncertainty In the Lidar Radial Velocitymentioning
confidence: 99%
See 2 more Smart Citations
“…A basic spike filter was evaluated for the model in addition to several methods developed by Lenschow et al (2000). The spike filter routine used in this work was based on one of the lidar preprocessing steps presented by Wang et al (2015). First, the difference between adjacent velocity values, v, is calculated for all velocity measurements in a 10 min period, defined by the following equation:…”
Section: Instrument Noisementioning
confidence: 99%